MEDIDAS PROFILÁTICAS PARA PROTEGER MADEIRAS À AÇÃO DE INSETOS XILÓFAGOS - Pinto, Joyce de Almeida (2020)
The Order Coleoptera, belonging to the Insecta Class, has great prominence in the forest environment. However, there is a need for studies that report the beetles that commonly attack processed wood in different environments, as well as their preference i